Macroprolactinemia in a Patient with Invasive Macroprolactinoma: A Case Report and Minireview - Atanaska Elenkova; Zdravka Abadzhieva; Nikolai Genov; Vladimir Vasilev; Georgi Kirilov; Sabina Zacharieva (Case Reports in Endocrinology)
Background. Macroprolactin, the high-molecular prolactin isoform, is considered to be an inactive in vivo product with extrapituitary origin. Patients with macroprolactinemia are usually asymptomatic, with negative pituitary imaging. Based on these data, most authors do not recommend treatment and long-term followup in subjects with macroprolactinemia. However, there is evidence for overlapping clinical features among subjects with hyperprolactinemia due to monomeric or “big big” PRL isoform. Case Presentation. We present a 35-year-old female patient with secondary amenorrhea, mild obesity, hirsutism, headache and blurred vision. Hormonal evaluation revealed an extreme hyperprolactinemia (PRL = 10 610 mIU/L) almost exclusively due to macroprolactin isoform (MPRL = 10 107 mIU/L; recovery after PEG precipitation 4.7%) and hypogonadotropic hypogonadism. An invasive pituitary macroadenoma was visualized on MRI, and cabergoline therapy was initiated. Disappearance of clinical signs and symptoms, normalization of gonadotropin levels, and restoration of regular ovulatory menstrual cycles after 1 year of treatment are arguments in favor of preserved-macroprolactin bioactivity in this case. The significant decrease in MPRL levels and tumor volume in response to dopamine agonist therapy is suggestive for the tumoral origin of this isoform. Conclusions. Although macroprolactinemia is considered to be a benign condition, pituitary imaging, dopamine agonist treatment, and prolonged followup should be recommended in some particular cases.